PERLINDUNGAN KONSUMEN ATAS PRODUK MAKANAN MIE BASAH YANG MENGANDUNG ZAT BERBAHAYA BERDASARKANUNDANG - UNDANG NOMOR 8 TAHUN1999 TENTANG PERLINDUNGAN KONSUMEN KOTA PEKANBARU - Haziat, Martin; Heriyanti, Yuli; Sutrisno, Hafiz (Pahlawan Tuanku Tambusai University, 2024)
Consumer protection is all efforts to ensure legal certainty to provide protection to consumers. Legal certainty to protect consumer rights, which is strengthened through the Law on Consumer Protection and other legal instruments. The legal basis for Consumer Protection is the Consumer Protection Law Number 8 of 1999 concerning Consumer Protection. Type and nature of this research is empirical, namely research with field data as the main data source such as the results of interviews and observations. The results of this research in the first discussion are that the public as consumers are protected by Article 86 paragraph (1) of Law Number 18 of 2012 concerning Food. Apart from that, consumer protection for wet noodles is also carried out in 2 ways. The first is preventive protection, namely protection provided by the government before a violation occurs. The second is repressive legal protection, namely protection, namely final protection such as fines. The second discussion is that the main factor causing many people as consumers to suffer losses is the lack of consumer insight itself, proven by the author's field survey and analysis. The second factor is that the distribution of wet noodles is not only bought and sold only in traditional markets, but also distributed via E-Commerce (Online). Keywords : Consumer Protection, Food Products, Wet Noodles.